Sex Differences in a Semantic Fluency Task - Federico Soriano; Julieta Fumagalli; Diego Shalóm; Julia Carden; Geraldine Borovinsky; Facundo Manes; Macarena Martínez-Cuitiño (East European Journal of Psycholinguistics, 2015)
It is a well-documented empirical fact that men and women perform differently in language tasks involving various semantic categories. The sex-by-category effect has been reported in several languages and through different tasks. The results of these studies agree that some semantic categories are preferentially male while others are preferentially female, but which categories are associated with one gender or the other varies across studies. In our study, we tested a group of undergraduate native Spanish speakers from Argentina on a written semantic fluency task. Participants were tested on ten semantic categories, five from the Living Things domain (LT) and five from the Non-Living Things domain (NLT). While women retrieved more items than men across categories, differential output was only significant in five categories: animals, vegetables (LT), furniture and utensils (NLT) for females and tools (NLT) for males.ReferencesBarbarotto, R., Laiacona, M., & Capitani, E. (2008). Does sex influence the age ofacquisition of common names? A contrast of different semantic categories. Cortex, 44(9), 1161–1170. doi: http://dx.doi.org/10.1016/j.cortex.2007.08.016Barbarotto, R., Laiacona, M., Macchi, V., & Capitani, E. (2002). Picture realitydecision, semantic categories and gender. A new set of pictures, with norms and an experimentalstudy. Neuropsychologia, 40, 1637–1653. doi: http://dx.doi.org/10.1016/S0028-3932(02)00029-5Barbarotto, R., M. Laiacona & E. Capitani. (2008). Does sex influence the age ofacquisition of common names? A contrast of different semantic categories. Cortex, 44(9), 1161–1170.Capitani, E., Laiacona, M., & Barbarotto, R. (1999). Gender affects word retrieval ofcertain categories in semantic fluency tasks. Cortex, 35, 273–278. doi:http://dx.doi.org/10.1016/S0010-9452(08)70800-1Caramazza, A., & Shelton, J. R. (1998). Domain-specific knowledge systems in thebrain: The animate-inanimate distinction Journal of Cognitive Neuroscience, 10, 1–34. doi:http://dx.doi.org/10.1162/089892998563752Gainotti, G., Ciaraffa, F., Silveri, M. C., & Marra, C. (2010). Different views about thenature of gender-related asymmetries in task based on biological or artefact categories.Behavioural Neurology, 22(3–4), 81–90. doi: http://dx.doi.org/10.1155/2010/410858Gainotti, G., P. Spinelli et al. (2012). Asymmetries in gender-related familiarity withdifferent semantic categories. Data from normal adults. Behavioural Neurology, 27(2), 175–181.